Multidisciplinary approach in restoring а severely destroyed upper premolar: Case report - Krasimir Tsvetanov (LLC "Endo Press", 2020)
Clinicians often have to deal with severely destroyed teeth. One of the keys to long-term success of the prosthetic restorations is the presence of "ferrule" effect. This case report describes how а proper ferrule effect of tooth 2.5 was achieved with the rapid orthodontic extrusion and restored with ceramic-layered zirconium.